Construction of micro-nano robots: living cells and functionalized biological cell membranes - Niu, Jiawen; Liu, Chenlu; Yang, Xiaopeng; Liang, Wenlong; Wang, Yufu (Frontiers in Bioengineering and Biotechnology, 2023)
Micro-nano robots have emerged as a promising research field with vast potential applications in biomedicine. The motor is the key component of micro-nano robot research, and the design of the motor is crucial. Among the most commonly used motors are those derived from living cells such as bacteria with flagella, sperm, and algal cells. Additionally, scientists have developed numerous selfadaptive biomimetic motors with biological functions, primarily cell membrane functionalized micromotors. This novel type of motor exhibits remarkable performance in complex media. This paper provides a comprehensive review of the structure and performance of micro-nano robots that utilize living cells and functionalized biological cell membranes. We also discuss potential practical applications of these mirco-nano robots as well as potential challenges that may arise in future development.1 This is a provisional file, not the final typeset article Over the past decade, significant advancements have been made in the design and production of micromotors that utilize various driving methods (